PEMBERIAN EKSTRAK DAUN KETAPANG UNTUK MENINGKATKAN IMUN – NON SPESIFIK PADA IKAN (ARTIKEL REVIEW) - MUAHIDDAH, NURI; SUMSANTO, MUHAMMAD (GANEC SWARA, 2023)
This review article focuses on the administration of ketapang leaf extract to enhance non-specific immunity in fish. Ketapang leaves have been of interest as a potential immunostimulant in aquaculture to boost the non-specific immune response in fish. In this review, various studies exploring the effects of ketapang leaf extract on the non-specific immune response of fish have been examined. The findings suggest that the administration of ketapang leaf extract can lead to an increase in non-specific immune parameters, such as phagocytosis activity, lysozyme activity, and total protein content. The potential use of ketapang leaf extract as an immunostimulant in aquaculture shows promising results in enhancing the non-specific immune response of fish. Strengthening the non-specific immune system can help fish combat various pathogens and diseases, thereby improving their overall health and survival in aquaculture settings. However, further research is needed to fully understand the mechanisms of action and optimal dosage of ketapang leaf extract as an immunostimulant. Additionally, considering its potential positive impact on fish health, the use of ketapang leaf extract in aquaculture warrants comprehensive studies to ensure its safe and effective implementation.